Distinguishing High-Performing From Low-Performing Hospitals for Severe Maternal Morbidity: A Focus on Quality and Equity. Issue 6 (2nd June 2022) - Howell, Elizabeth A.; Sofaer, Shoshanna; Balbierz, Amy; Kheyfets, Anna; Glazer, Kimberly B.; Zeitlin, Jennifer
Abstract : Organizational factors, policies, and practices at multiple levels distinguish high-performing from low-performing hospitals for severe maternal morbidity. Abstract : OBJECTIVE: To investigate which organizational factors, policies, and practices distinguish hospitals with high compared with low risk-adjusted rates of severe maternal morbidity (SMM). METHODS: Using a positive deviance approach, this qualitative study included 50 semistructured interviews with health care professionals (obstetrics and gynecology chairs, labor and delivery medical directors, nurse managers, frontline nurses, physicians or nurses responsible for quality and safety, and chief medical officers) in four low-performing and four high-performing hospitals in New York City. Hospital performance was based on risk-adjusted morbidity metrics from previous research. Major topics explored were structural characteristics (eg, staffing, credentialing), organizational characteristics (eg, culture, leadership, communication, use of data), labor and delivery practices (eg, use of standardized, evidence-based practices, teamwork), and racial and ethnic disparities in SMM. All interviews were audiotaped, professionally transcribed, and coded using NVivo software. Researchers blinded to group assignment conducted qualitative content analysis. Researchers wrote analytic memos to identify key themes and patterns emerging from the interviews, highlight illustrative quotes, and draw qualitative comparisons between the two hospital clusters with different (but unrevealed) performance levels. RESULTS: Six themes distinguished high-performing from low-performing hospitals. High-performing hospitals were more likely to have: 1) senior leadership involved in day-to-day quality activities and dedicated to quality improvement, 2) a strong focus on standards and standardized care, 3) strong nurse–physician communication and teamwork, 4) adequate physician and nurse staffing and supervision, 5) sharing of performance data with nurses and other frontline clinicians, and 6) explicit awareness that racial and ethnic disparities exist and that racism and bias in the hospital can lead to differential treatment. CONCLUSION: Organizational factors, policies, and practices at multiple levels distinguish high-performing from low-performing hospitals for SMM. Findings illustrate the potential for targeted quality initiatives to improve maternal health and reduce obstetric disparities arising from delivery in low-performing hospitals.